MEKTEPLERDE QARAQALPAQ ÁDEBIYATÍN OQÍTÍWDA MILLIY QÁDIRIYATLARDÍ SIŃDIRIWDIŃ PEDAGOGIKALÍQ TIYKARLARÍ - Embergenova, Mapruza Abdiualiyevna; Kalmurzaeva, Xurliman Xojabaevna (SCIENCE and SOCIETY, 2026)
This article examines the issues of instilling national values in the teaching of Karakalpak literature in schools. Through literary works, the ways of enriching the spiritual world of students and shaping their patriotic, humanistic, and national consciousness are analyzed. The importance of interactive methods, the use of folklore materials, and interdisciplinary connections will also be emphasized. The research results will provide practical recommendations for increasing the effectiveness of instilling national values in Karakalpak literature lessons.